The Potato Aphid Salivary Effector Me47 Is a Glutathione-S-Transferase Involved in Modifying Plant Responses to Aphid Infestation - Kettles, Graeme J.; Kaloshian, Isgouhi (Frontiers in Plant Science, 2016)
Polyphagous aphid pests cause considerable economic damage to crop plants, primarily through the depletion of photoassimilates and transfer of viruses. The potato aphid (Macrosiphum euphorbiae) is a notable pest of solanaceous crops, however the molecular mechanisms that underpin the ability to colonize these hosts are unknown. It has recently been demonstrated that like other aphid species, M. euphorbiae injects a battery of salivary proteins into host plants during feeding. It is speculated that these proteins function in a manner analagous to secreted effectors from phytopathogenic bacteria, fungi and oomycetes. Here we describe a novel aphid effector (Me47) which was identified from the potato aphid salivary secretome as a putative glutathione-S-transferase (GST). Expression of Me47 in Nicotiana benthamiana enhanced reproductive performance of green peach aphid (Myzus persicae). Similarly, delivery of Me47 into leaves of tomato (Solanum lycopersicum) by Pseudomonas spp. enhanced potato aphid fecundity. In contrast, delivery of Me47 into Arabidopsis thaliana reduced GPA reproductive performance, indicating that Me47 impacts the outcome of plant-aphid interactions differently depending on the host species. Delivery of Me47 by the non-pathogenic Pseudomonas fluorescens revealed that Me47 protein or activity triggers defense gene transcriptional upregulation in tomato but not Arabidopsis. Recombinant Me47 was purified and demonstrated to have GST activity against two specific isothiocyanates (ITCs), compounds implicated in herbivore defense. Whilst GSTs have previously been associated with development of aphid resistance to synthetic insecticides, the findings described here highlight a novel function as both an elicitor and suppressor of plant defense when delivered into host tissues.